Tiffany Girl [large type] : a novel - Gist, Deeanne (Center Point Large Print, 2015)
"When a glassworker's strike threatened Louis Tiffany's dream of creating his stained glass mosaic chapel, he hand-picked art student Flossie Jayne to help complete the task. As an independent "New Woman" she races to complete the Tiffany chapel and make a name for herself in the art world--and learns some important lessons about life and love"--